MENINGKATKAN HASIL BELAJAR IPAS MATERI TATA SURYA DENGAN MENGGUNAKAN MEDIA ARTICULATE STORYLINE PADA SISWA KELAS VI SD NEGERI 067241 MEDAN DENAI - Indah Sri Annisa; M Fauzi Hasibuan; Lasma Silaban (STKIP Subang, 2024)
This research focuses on the low learning outcomes of IPAS on Solar System material in class VI SD Negeri 067241 Medan Denai. This study aims to improve student learning outcomes through articulate storyline learning media. The method used is Classroom Action Research (PTK) which includes four stages: planning, action, observation, and reflection. The subjects of this study were 27 grade VI students. Data were collected through observation and tests. The results showed a significant improvement in learning outcomes after the use of articulate storyline media. Before the action, only 30% of students reached the Minimum Completion Criteria (KKM). After the application of articulate storyline media, the percentage increased to 52% in cycle I and reached 89% in cycle II. The average score of students also increased from 61.4 in preaction to 69.6 in cycle I, and 85.1 in cycle II.